Effect of Caries Infiltration Technique and Fluoride Therapy on Microhardness of Enamel Carious Lesions - Torres, C. R. G. [UNESP]; Rosa, P. C. F. [UNESP]; Ferreira, N. S. [UNESP]; Borges, Alessandra Buhler [UNESP] (Operative Dentistry Inc, 2012)
Enamel white spot subsurface lesions compromise esthetics and precede cavitation; therefore, they must be halted. The aim of this study was to evaluate the effect of a caries infiltration technique and fluoride therapy on the microhardness of enamel carious lesions. Subsurface carious lesions were produced in 60 bovine specimens with polished enamel surfaces. The specimens were divided into four groups (n=15), according to the treatment used: CON, control immersion in artificial saliva; DF, daily 0.05% fluoride solution; WF, weekly 2% fluoride gel; and IC, resin infiltration (Icon). The specimens were kept in artificial saliva and evaluated for microhardness at five points: baseline, after caries production, after four and eight weeks of treatment, and a final evaluation after being submitted to a new acid challenge. The repeated-measures analysis of variance showed significant differences according to the type of treatment (TREAT; p=0.001) and time of evaluation (EV; p=0.001). The results of the Tukey test were TREAT: CON = 45.18 (+/- 29.17)a, DF = 107.75 (+/- 67.38)b, WF = 83.25 (+/- 51.17)c, and IC = 160.83 (+/- 91.11)d. Analysis of correlation between the TREAT and EV factors showed no significant differences for DF (138.63 +/- 38.94) and IC (160.99 +/- 46.13) after the new acid challenge. The microhardness results in decreasing order after eight weeks were IC > DF > WF > CON. It was concluded that the microhardness of carious lesions increased with the infiltration of resin, while the final microhardness after a new acid challenge was similar for DF and IC.